2016
DOI: 10.1039/c5fd00153f
|View full text |Cite
|
Sign up to set email alerts
|

Design and stabilisation of a high area iron molybdate surface for the selective oxidation of methanol to formaldehyde

Abstract: The performance of Mo-enriched, bulk ferric molybdate, employed commercially for the industrially important reaction of the selective oxidation of methanol to formaldehyde, is limited by a low surface area, typically 5-8 m(2) g(-1). Recent advances in the understanding of the iron molybdate catalyst have focused on the study of MoOx@Fe2O3 (MoOx shell, Fe2O3 core) systems, where only a few overlayers of Mo are present on the surface. This method of preparing MoOx@Fe2O3 catalysts was shown to support an iron mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…2. The minor changes were a shifting of the peak to higher temperature by B20 1C, and a broadening of the peaks, similar to those previously reported by Chapman et al 6 TPD for the four Al loadings are shown in Fig. S5 (ESI †).…”
Section: Reactivity Studies Of Hsa Fe 2 Osupporting
confidence: 86%
See 3 more Smart Citations
“…2. The minor changes were a shifting of the peak to higher temperature by B20 1C, and a broadening of the peaks, similar to those previously reported by Chapman et al 6 TPD for the four Al loadings are shown in Fig. S5 (ESI †).…”
Section: Reactivity Studies Of Hsa Fe 2 Osupporting
confidence: 86%
“…[14][15][16][17][18] Initial studies of Al-doped haematite have been conducted as support materials in shell-core selective oxidation catalysts. 6 It was found that the incorporation of 5 wt% Al into Fe 2 O 3 doubled the surface area of the post-calcination material, while essentially retaining the corundum structure. Subsequently, after adding MoO x shell layers to the Al-doped Fe 2 O 3 and assessing the reactivity of the resulting catalysts, it was determined that the greater surface area of the catalyst reduced the requisite operating temperature of the catalyst by approximately 20 1C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction measurements were carried out in a Hiden Catlab using its pulsed flow reactor capability . 0.22 g of catalyst was loaded into the quartz reactor tube and heated in‐situ prior to reaction to 250 °C in 10 % H 2 in He, followed a pure He flow for one hour prior to the pulsing experiments.…”
Section: Methodsmentioning
confidence: 99%